The role of steric hindrance in the intramolecular oxidative aromatic coupling of pyrrolo[3, 2-b]pyrroles. Issue 77 (5th September 2016) - Krzeszewski, Maciej; Świder, Paweł; Dobrzycki, Łukasz; Cyrański, Michał K.; Danikiewicz, Witold; Gryko, Daniel T.
Abstract : Sterically hindered tetraaryl-pyrrolo[3, 2- b ]pyrroles undergo oxidative aromatic coupling, forming a fluorene scaffold linked via a spiro carbon atom with a novel π-conjugated scaffold. Abstract : The presence of steric hindrance triggers different reaction pathways in the intramolecular oxidative aromatic coupling of tetraaryl-pyrrolo[3, 2- b ]pyrroles and leads to the formation of a fluorene moiety and a new cationic π-system linked together by a spiro carbon atom. Computational studies elegantly rationalized these results. These previously unknown functional dyes emit red light with reasonable efficiency.